STRATEGIC ROLE OF ISLAMIC RELIGIOUS EDUCATION IN STRENGTHENING CHARACTER EDUCATION IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Muhamad Taufik (Universitas Islam Negeri Ar-Raniry, 2020)
Islamic Education plays a strategic role in the strengthening of character education in the era of the industrial revolution 4.0. Trends in automation, data exchange, Artificial intelligence, internet of things, 3D printing, robots and intelligent machines are massively replacing human labor. Disclosure of information access enables people receive a variety of information and can affect even change the character, way of thinking and behaving. Here, the role of Islamic Education as a facilitator who runs the cultural function and ideal function as a control value and steers the development of society. Strengthened with social reconstruction curriculum so that learning is more focused on the problems-problems encountered in the community so that students are able to adapt to the development of the modern world and highly competitive yet-holistic integrative religious character so as to fortify the morale of the nation's poor from the impact of globalization. Strengthening the Character Education through Islamic education has a significant contribution to the ideals of national education as a form of educational investment in creating a golden generation in the era of the global arena by establishing a balance hard skills and soft skills, which in turn will create a community culture of learning (learning society).